HUMANITY AND TECHNOLOGY:: ETHICAL AND PHILOSOPHICAL IMPLICATIONS (REMUNOM, 2024)
This article explores the complex ethical and philosophical issues that arise with the development of new technologies, addressing their potential benefits, such as increased productivity, improved services and the resolution of global problems, while warning about their risks, such as algorithmic discrimination, loss of human control over electronic systems, climate change and the Anthropocene. The study also examines the different ethical principles that can be used to guide the development and use of artificial intelligence, such as the principle of beneficence, the principle of non-maleficence, the principle of justice and the principle of autonomy, in addition to establishing connections between technological advances and areas of philosophy, such as Transhumanism and Futurology, in the development of a solid ethical framework to ensure that it is used responsibly and beneficially for humanity.